High level Antarctic EIA under the Madrid Protocol: state practice and the effectiveness of the Comprehensive Environmental Evaluation process. - Hemmings, AD; Kriwoken, L (International Environmental Agreements: Politics, Law and Economics, 2010)
The 1991 Protocol on Environmental Protection to the Antarctic Treaty (Madrid Protocol), the latest instrument of the Antarctic Treaty system (ATS), establishes environmental standards to manage 10% of the planet. Under the Madrid Protocol, all activities subject to advance notice reporting obligations under the 1959 Antarctic Treaty are required to undergo prior Environmental Impact Assessment (EIA). The highest level EIA—termed a Comprehensive Environmental Evaluation (CEE)—requires international scrutiny. This is the only form of EIA where such scrutiny occurs and the only context under the Madrid Protocol or any other part of the ATS where the proposed actions of State Parties, or operators subject to their jurisdiction, are subject to formal international review. Whilst this review does not provide a veto, it has been viewed as an important development in the Antarctic multilateral regime. To date, there have been 19 CEEs. This article reviews the Antarctic CEE process and evaluates its application in practice against the environmental obligations established in the Protocol. Whilst most CEEs are substantial documents and processes, which have raised the standard of environmental care in the area, there are significant generic limitations. Not one CEE appears to have led to substantial modification of the activity as first elaborated by the proponent, let alone a decision not to proceed with the activity, despite this being a mandatory consideration. There are indications that the imperatives in the CEE process are often administrative and diplomatic rather than environmental and that notwithstanding the international scrutiny of draft CEEs, state action may not be significantly changed. Suggestions are made on improvements to the CEE process. The Madrid Protocol is a framework convention, designed so that its technical annexes, including that addressing EIA, may be periodically updated.